#AllAfricanlivesMatter: Race, Gender, and the Relevance of Global Pan-African Solidarity - Daley, P. (My University, 2016)
The talk will situate the emerging black lives matter movements in the USA and UK in the historical Pan-African struggle for African liberation, and asks why does the current movement seem to have so little visible support on the African continent, especially in the light of the African diaspora being the African Union 6th region and in the midst of the UN’s international decade for people of African descent. Drawing on research in feminist geo-politics, Critical Race Theory, and Pan-African and decolonial thought, and will explore the continued coloniality of contemporary existence by exploring how racialized and gendered hierarchies have been central to the building and maintenance of the global political and economic order – even under the supposed ‘racelessness’ of neo-liberalism. These have been brought to the fore with the Trump victory in the USA. Cross–continental commonalities in the de-humanization of African lives will be examined using a brief illustration of the approaches to sexual violence against women racialized as black on the continent and in the African diaspora. The discussion will conclude with a discussion of how an emancipatory de-colonial Pan-African solidarity can be harnessed.
Seminar
Keywords: Pan-African struggle; African liberation; African liberation; racelessness